Sex Differences in Hypothalamic Changes and the Metabolic Response of TgAPP Mice to a High Fat Diet - Freire-Regatillo, Alejandra; Diaz-Pacheco, Sonia; Frago, Laura M.; Arévalo, María-Ángeles; Argente, Jesús; Garcia-Segura, Luis M.; de Ceballos, María L.; Chowen, Julie A. (Frontiers in Neuroanatomy, 2022)
The propensity to develop neurodegenerative diseases is influenced by diverse factors including genetic background, sex, lifestyle, including dietary habits and being overweight, and age. Indeed, with aging, there is an increased incidence of obesity and neurodegenerative processes, both of which are associated with inflammatory responses, in a sex-specific manner. High fat diet (HFD) commonly leads to obesity and markedly affects metabolism, both peripherally and centrally. Here we analyzed the metabolic and inflammatory responses of middle-aged (11–12 months old) transgenic amyloid precursor protein (TgAPP) mice of both sexes to HFD for 18 weeks (starting at 7–8 months of age). We found clear sex differences with females gaining significantly more weight and fat mass than males, with a larger increase in circulating leptin levels and expression of inflammatory markers in visceral adipose tissue. Glycemia and insulin levels increased in HFD fed mice of both sexes, with TgAPP mice being more affected than wild type (WT) mice. In the hypothalamus, murine amyloid β (Aβ) levels were increased by HFD intake exclusively in males, reaching statistical significance in TgAPP males. On a low fat diet (LFD), TgAPP males had significantly lower mRNA levels of the anorexigenic neuropeptide proopiomelanocortin (POMC) than WT males, with HFD intake decreasing the expression of the orexigenic neuropeptides Agouti-related peptide (AgRP) and neuropeptide Y (NPY), especially in TgAPP mice. In females, HFD increased POMC mRNA levels but had no effect on AgRP or NPY mRNA levels, and with no effect on genotype. There was no effect of diet or genotype on the hypothalamic inflammatory markers analyzed or the astrogliosis marker glial acidic protein (GFAP); however, levels of the microglial marker Iba-1 increased selectively in male TgAPP mice. In summary, the response to HFD intake was significantly affected by sex, with fewer effects due to genotype. Hypothalamic inflammatory cytokine expression and astrogliosis were little affected by HFD in middle-aged mice, although in TgAPP males, which showed increased Aβ, there was microglial activation. Thus, excess intake of diets high in fat should be avoided because of its possible detrimental consequences.